Antimicrobial Efficacy, Secondary Metabolite Constituents, Ligand Docking of Enantia chlorantha on Selected Multidrug Resistance Bacteria and Fungi - Oluwatoyin Modupe Aladejana (Journal of Advances in Biology & Biotechnology, 2020)
This study aimed at determining the phytochemical constituents and antimicrobial efficacy of Enantia chlorantha on multidrug resistance microorganisms.And also to study the interaction of plant secondary metabolite (phytochemicals) from Enantia chlorantha with three proteins. Antimicrobial activity of the extracts of E. chlorantha (leaf and stem bark) against selected microorganisms was done using agar well diffusion method. Minimum inhibitory concentrations (MICs), minimum bactericidal concentrations (MBCs) were also determined using standard methods. The qualitative and quantitative phytochemical screening of E. chlorantha were also determined. The molecular docking was determined using in-silico techniques and was elucidated. Protein generation, Ligand generation and Ligand Docking using GLIDE were determined. Standard precision (SP) flexible ligand docking was carried out in Glide of Schrödinger-Maestro 11.1 and the extra-precision (XP) mode. The crude extracts tested showed antimicrobial activities against all the test bacterial and fungal isolates for the stem bark extract while the leaf extract showed antimicrobial activities against some of the isolates with little differences. The zones of inhibition ranges between 9mm-24mm at 100mg/ml for the ethanol extract and 10mm-13mm at 12.5mg/ml. The Minimum Inhibitory Concentration (MIC) at which the isolates were sensitive to the various extracts differed and the MIC values ranged from 12.5mg/ml to 100mg/ml while the MBC for the organisms ranged from 25mg/ml to 100mg/ml.The qualitative phytochemical screening of Enantia chlorantha leaf and stem bark revealed the presence of medicinally active constituent such as cardiac glycoside, steroids, anthraquinone, tannin, saponin, phenol, and reducing sugar. The quantitative phytochemical screening of E. chlorantha stem bark and leaf using different solvents, showed the presence of different phytoconstituents in different quantities. Molecular docking results revealed some components of the plant to be more active compared to levofloxacin by inhibiting topoisomerase IV. Jartrorrhizine-1 and canadine-1 present in Enantia chlorantha have docking scores of -2.267 and 1.625 respectively which are greater than that of levofloxacin (-1.557) against Salmonella typhi. For Staphylococcus aureus, Argentine.sdf (-7.373) and Jartrorrhizine.sdf (-4.225) have high docking scores compared to Levofloxacin.sdf (-3.436) as well as Candida albican.The promising evidence for the antimicrobial effects of E. chlorantha against bacterial and fungal isolates in this study especially the stem bark extract showed that Enantia chlorantha is more effective at treating diseases caused by Salmonella typhi and other organisms and therefore can be used as an alternative source of therapeutic agents.